POTENCY OF AGAINST LEAF SPOT AND GROWTH PROMOTION TRAITS OF MAIZE (Journal of Plant Disease Sciences, 2025)
This study investigates the potential of five strains (designated Bb1 to Bb5) as biocontrol agents against , the pathogen responsible for turcicum leaf blight and plant growth promotion of maize. Among the tested strains, Bb1 demonstrated the most significant antagonistic activity, achieving an impressive 81.67% inhibition of growth . The study also assessed the plant growth promoting traits of Bb1, revealing that it exhibited 69.93% iron chelation efficiency, 60.67% phosphate solubilization efficiency and indole-3-acetic acid (IAA) production of 18.98 μg/ml. Overall, Bb1 stands out as a dual-function agent that is effective against while also enhancing plant growth.
Keywords: Beauveria bassiana, biocontrol, turcicum leaf blight, siderophore production, phosphate solubilization